2020
DOI: 10.5152/tud.2019.19191
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of bupivacaine alone and in a combination with lidocaine for caudal block in patients undergoing circumcision: A historical cohort study

Abstract: Ali Serdar Gözen, et al.; Robot-assisted vasovasostomy and vasoepididymostomy: Current status and review of the literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…In previous studies, local anaesthetic combinations were used for regional anaesthesia, creating favourable results with regard to the onset and duration of anaesthesia [ 31 33 ]. The literature published by Cubillon et al [ 34 ] compared mixtures of long-acting local anaesthetics such as ropivacaine or bupivacaine with lidocaine-induced faster onset blocks and decreased duration for femoral-sciatic nerve blockade.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, local anaesthetic combinations were used for regional anaesthesia, creating favourable results with regard to the onset and duration of anaesthesia [ 31 33 ]. The literature published by Cubillon et al [ 34 ] compared mixtures of long-acting local anaesthetics such as ropivacaine or bupivacaine with lidocaine-induced faster onset blocks and decreased duration for femoral-sciatic nerve blockade.…”
Section: Discussionmentioning
confidence: 99%
“…Bupivacaine and lidocaine are among the most common local anesthetics used in epidural analgesia. According to Atasever et al cohort study [16], combination of these two local anesthetics found to be safe and effective for caudal block in circumcision surgery. Moreover, their combination is widely used for labor analgesia [17].…”
Section: Discussionmentioning
confidence: 99%
“…Regional techniques such as caudal and pudendal blocks are also effective but rather invasive. 8 Dorsal penile nerve block (DPNB) and topical anesthetics such as lidocaine–prilocaine cream (LPC) are safe and commonly used techniques. 9 Many studies have shown that DPNB is more effective than topical LPC.…”
Section: Introductionmentioning
confidence: 99%
“…General anesthesia is effective but has high relative risks. Regional techniques such as caudal and pudendal blocks are also effective but rather invasive 8. Dorsal penile nerve block (DPNB) and topical anesthetics such as lidocaine–prilocaine cream (LPC) are safe and commonly used techniques 9.…”
Section: Introductionmentioning
confidence: 99%